2014
DOI: 10.1002/ejhf.55
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐specific health status as a predictor of mortality in patients with heart failure: a systematic literature review and meta‐analysis of prospective cohort studies

Abstract: Aims Some, but not all, studies have shown that patient‐reported health status, including symptoms, functioning, and health‐related quality of life, provides additional information to traditional clinical factors in predicting prognosis in heart failure patients. To evaluate the overall evidence, the association of disease‐specific health status on mortality in heart failure was examined through a systematic review and meta‐analysis. Methods and results Prospective cohort studies that assessed the independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 49 publications
0
43
0
2
Order By: Relevance
“…In recent years HRQOL and patient-reported health status have gained considerable interest on various levels. 178 Cardiac patients with poor self-reported HRQOL tend to have higher rates of re-infarction and rehospitalisation, 179,180 and they are less likely to be invited to, or to attend CR.…”
mentioning
confidence: 99%
“…In recent years HRQOL and patient-reported health status have gained considerable interest on various levels. 178 Cardiac patients with poor self-reported HRQOL tend to have higher rates of re-infarction and rehospitalisation, 179,180 and they are less likely to be invited to, or to attend CR.…”
mentioning
confidence: 99%
“…1 We have been able to establish why the Systolic Heart failure treatment with the I f inhibitor ivabradine Trial (SHIFT) study was not identified in our original search. The original search was conducted as follows: (quality of life OR health status OR self-rated health OR functional status OR functioning) AND (hospitalization OR readmission OR mortality OR survival OR prognosis) AND (heart failure OR CHF), with 'hospitalization' as 'MeSH' term and other search terms using 'Title/Abstract'.…”
mentioning
confidence: 99%
“…Studies were included in the review if they (1) included HF patients and their respective informal family caregivers; (2) measured or described relationship quality chosen because (1) mortality is considered the ''single best measure of health'' 27(p721) because it is 1 of the most reliable and a valid measures of health available and (2) health status, 28 distress or depressive symptoms, 29 and caregiver burden 5 have all been shown to be related to mortality risk. Studies were excluded if they were unpublished manuscripts (abstracts or dissertations), case studies, reviews of the literature, or not available in English.…”
Section: Literature Searchmentioning
confidence: 99%